CSF hydrodynamics in superior sagittal sinus thrombosis. Issue 4 (April 1992) - Kristensen, B; Malm, J; Markgren, P; Ekstedt, J
Abstract : Cerebrospinal fluid hydrodynamics were investigated with a constant pressure infusion method in patients with superior sagittal sinus thrombosis. Ten patients were studied with serial examinations up to 15 years after the onset of the disease. A total of 70 CSF hydrodynamic examinations were performed. A clear increase in intracranial pressure due to raised pressure in the major dural sinus was seen in all patients. A striking feature was the persistent intracranial pressure increase that declined only gradually. This had no obvious clinical impact. Change in CSF resorption facility played only a minor role in the intracranial pressure elevation. None of the patients developed hydrocephalus.